FRACTURE COMPLEXITY AND IMPLANT COSTS IN MAXILLOFACIAL TRAUMA PATIENTS UNDERGOING OPEN REDUCTION AND INTERNAL FIXATION - Iwan Setiawan Adji; Namira Aisya Devi; Hanif Nur Khairuddin; Eillena Noxie Azzahra; Zahira Husna Aflaha Khansa Siswaya; Sultan Bayu Fahmi; Betty Dwi Yuliyanti; Farid Adi Prasetya (Journal of World Future Medicine, Health and Nursing, 2026)
Maxillofacial trauma frequently requires open reduction and internal fixation (ORIF) using various implant systems that may increase operative costs, particularly in complex fractures. This study aimed to analyze the relationship between fracture complexity and implant costs in maxillofacial trauma patients undergoing ORIF. A retrospective cross-sectional study was conducted using retrospective medical records from 35 patients treated at PKU Muhammadiyah Karanganyar Hospital during 2025–2026. Statistical analysis was performed using the Shapiro–Wilk test and the Independent Samples T-Test. Most patients were male (80.0%) with a mean age of 36.86 ± 18.44 years. Simple fractures accounted for 57.1% of cases, whereas complex fractures accounted for 42.9%. A total of 66 implant components were used during ORIF procedures, with AT-DRV screws accounting for the largest proportion (69.7%). while multiple-point fixation was the most common fixation strategy (40.0%). The mean implant cost was 6.80 ± 3.76 million rupiahs. Statistical analysis showed no statistically significant association between fracture complexity and implant cost (p = 0.845). However, interpretation is limited by the retrospective design and small sample size (n = 35) may have limited the statistical power to detect a true association. Furthermore, the retrospective study design limits causal inference and depends on the completeness and accuracy of the available medical records.